2022
DOI: 10.21512/tw.v23i1.7078
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perceived Usefulness and Perceived Easiness towards Behavioral Intention to Use Fintech by Indonesian MSMEs

Abstract: The research aimed to test how are Micro Small Medium Enterprise (MSMEs) acceptance towards financial technology  fintech). The number of MSME that using fintech is still need to be maximized. MSMEs were chosen as research object due to their numerous contribution in gross domestic product (GDP). Therefore, it was considered important to understand MSME’s notion to use fintech in their business operation, which is wellknown that financial technology could give a lot of services which may improve MSMEs performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 13 publications
1
8
0
1
Order By: Relevance
“…This shows that the more useful a system or information technology is for the work or activities of its users, the user will have an interest in continuing to use the system or information technology. Several previous studies found a significant influence of perceived usefulness on behavioral intention (Aris, 2015;Aris et al, 2016;Budi et al, 2021;Peng & Yan, 2022;Perwitasari, 2022;Widiar et al, 2023). However, several studies found an insignificant influence between perceived usefulness and behavioral intention (Muslichah, 2018;Nainggolan et al, 2023;Szajna, 1996).…”
Section: Technology Acceptance Modelmentioning
confidence: 93%
“…This shows that the more useful a system or information technology is for the work or activities of its users, the user will have an interest in continuing to use the system or information technology. Several previous studies found a significant influence of perceived usefulness on behavioral intention (Aris, 2015;Aris et al, 2016;Budi et al, 2021;Peng & Yan, 2022;Perwitasari, 2022;Widiar et al, 2023). However, several studies found an insignificant influence between perceived usefulness and behavioral intention (Muslichah, 2018;Nainggolan et al, 2023;Szajna, 1996).…”
Section: Technology Acceptance Modelmentioning
confidence: 93%
“…Fintech sekarang ini mempunyai peran yang sangat besar pada berbagai transaksi keuangan. Indonesia juga saat ini sedang mengalami peningkatan yang tinggi pada industri fintech (Perwitasari, 2022).…”
Section: Pendahuluanunclassified
“…Several factors can affect trust and customer loyalty, namely perceived ease of use and enjoyment. Perceived ease of use is a person's level of perception that using a certain system will be free or reduce the spent effort (Perwitasari, 2022). Ease of use can reduce individual effort, both time and energy, to learn and use technology.…”
Section: Introductionmentioning
confidence: 99%